REPRESENTASI TUGAS PEMBELAJARAN MEMBACA DALAM BUKU TEKS BAHASA INDONESIA - Rahmawati, Rima Marista; Nadia Elfira Liyani; Nia Sri Wahyuni; Yuan Yuniar; Maulida Isefani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Textbooks are one of the primary instructional resources used in Indonesian language learning in schools. One of their essential components is reading tasks designed to develop students' reading skills. This study aimed to identify and analyze the representation of reading tasks presented in an Indonesian language textbook, focusing on the types of reading tasks, the targeted cognitive levels, and their alignment with the scientific approach promoted by the Merdeka Curriculum. The study employed a document analysis method using a descriptive qualitative approach. The findings revealed that the reading tasks were predominantly concentrated at low to medium cognitive levels, whereas tasks designed to foster critical and creative thinking remained limited. These findings suggested that the textbook has not yet provided a balanced distribution of cognitive demands across reading activities. The study highlighted the need for textbook developers and teachers to design more diverse and cognitively challenging reading tasks that support comprehensive reading instruction and promote students' higher-order thinking skills in accordance with the objectives of the Merdeka Curriculum.